PERANCANGAN PORTAL BERITA DARING MAGAZINC! SEBAGAI MEDIA INFORMASI MAHASISWA - Mochammad Faizal; Nurul Arifin Aristarini (Jurnal Bahasa Rupa, 2020)
Magazinc! is one of the mass media managed by Telkom University students, which so far has only focused on publication activities through social media and print magazines. In 2019, Magazinc! do not have a news portal website even though they realize the importance of the website's presence. This article will describe the design process of the Magazinc! website through a mixed-method approach. The necessary data has been collected through triangulation of literature review related to students' news portal website design, interviews, questionnaires, and visual observations, to maximize the validity of this research. Based on the results of data analysis, we found that the typeface used on web pages largely determines the size that should be used for the typography itself. Also, a Magazinc! news portal website has been designed, which can compete with similar websites that already exist within Telkom University. This article can be an example of designing a student news portal website.